2009
DOI: 10.1073/pnas.0901002106
|View full text |Cite
|
Sign up to set email alerts
|

Universal oscillations in counting statistics

Abstract: Noise is a result of stochastic processes that originate from quantum or classical sources. Higher-order cumulants of the probability distribution underlying the stochastic events are believed to contain details that characterize the correlations within a given noise source and its interaction with the environment, but they are often difficult to measure. Here we report measurements of the transient cumulants ͗͗n m ͘͘ of the number n of passed charges to very high orders (up to m ‫؍‬ 15) for electron transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
235
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 20 publications
10
235
0
Order By: Relevance
“…For the 12th order values up to 145 are reached and the amplitude of the 15th cumulant already exceeds 10 000. This factorial increase was shown already for oscillations as function of time 12 and appears here again, showing the universal nature of the oscillations.…”
Section: Figsupporting
confidence: 76%
See 3 more Smart Citations
“…For the 12th order values up to 145 are reached and the amplitude of the 15th cumulant already exceeds 10 000. This factorial increase was shown already for oscillations as function of time 12 and appears here again, showing the universal nature of the oscillations.…”
Section: Figsupporting
confidence: 76%
“…14 The theoretical treatment has shown that these oscillations are a universally expected phenomenon for most physical systems and that in QDs they should show up prominently as function of the barrier asymmetry. 12,16 In this paper, we present the experimental verification of the predicted oscillations in the higher cumulants as function of barrier asymmetry in a QD system. To this aim we employ real time single electron counting with a high bandwidth detector.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…[5][6][7][8] Experimentally, high order transient cumulants of charge passing through a quantum point contact have been measured up to 15th cumulant and universal oscillations were found in counting statistics. 9 Theoretically, finite frequency FCS has been studied using quantum master equation and scattering matrix approach. [10][11][12][13] Less attention has been paid on FCS of transient transferred charge.…”
Section: Introductionmentioning
confidence: 99%